Legal Protection of Inheritance of Extramarital Children in the Chinese - Fatsya Gita Subagia; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The purpose of this research is to examine and analyze further the forms of inheritance protection for children born out of wedlock. The research method used is a normative juridical method, focusing on legal regulations, books, and related literature. The position of children born out of wedlock regarding inheritance issues certainly differs from legitimate children. Children born out of wedlock must fulfill certain conditions to obtain their inheritance rights, especially for children born out of wedlock within the Chinese community, which has customary regulations and legal conditions regarding the protection of their inheritance status. The research is conducted by studying the legal system related to legal regulations on the position, and inheritance status, and by examining secondary sources such as literature and expert opinions. The research analysis is conducted using a qualitative method. Thus, it will explain the inheritance status for children born out of wedlock within the Chinese community.